2017
DOI: 10.1097/mlr.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Claims-based Predictors of Overdose from a Large Medicaid Program

Abstract: Background Health systems may play an important role in identification of patients at-risk of opioid medication overdose. However, standard measures for identifying overdose risk in administrative data do not exist. Objective Examine the association between opioid medication overdose and 2 validated measures of non-medical use of prescription opioids within claims data. Research Design A longitudinal retrospective cohort study that estimated associations between overdose and non-medical use. Subjects Adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…Prescription opioids are a major cause of opioid‐related death, especially in older adults . PIP is associated with higher odds of nonfatal opioid overdose, fatal opioid overdose, and all‐cause mortality . In our study, age was by far the strongest predictor of undergoing PIP.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Prescription opioids are a major cause of opioid‐related death, especially in older adults . PIP is associated with higher odds of nonfatal opioid overdose, fatal opioid overdose, and all‐cause mortality . In our study, age was by far the strongest predictor of undergoing PIP.…”
Section: Discussionmentioning
confidence: 52%
“…Similar to other studies, we identified exposure to 1 or more types of PIP, including: High‐dose opioids, defined according to the daily dose equivalent for each individual in each month in milligram morphine equivalents (MME) (Supplementary Appendix S2). We considered an individual to have received high‐dose opioids if his or her prescriptions averaged MME of 100 mg/d or more in 3 or more separate months. Overlapping opioid and benzodiazepine prescriptions, defined as opioid and benzodiazepine prescriptions that overlapped by at least 1 day in 3 or more separate months. Multiple opioid prescribers, defined as 4 or more opioid prescribers in any 3‐month period. Multiple opioid pharmacies, defined as opioids from 4 or more pharmacies in any 3‐month period. Lack of a documented pain diagnosis, defined as receiving opioids for 3 consecutive months without a pain diagnosis code on a medical service claim (Supplementary Appendix S3). …”
Section: Methodsmentioning
confidence: 99%
“…12 Analyses of Medicaid data show, for instance, a marked increase for opioid medication overdose among those who misuse compared to those who do not. 13 Individuals involved in opioid medication misuse have a number of behavioral, mental, and physical health issues that increase risk for misuse, including co-occurring substance use disorders, 1419 mental health/psychiatric conditions, 17, 18, 2022 severe and chronic pain, 16, 19, 2224 and poor general health/quality of life. 17, 24 …”
Section: Introductionmentioning
confidence: 99%
“…Such behavior is problematic as consuming high opioid doses has the potential to elevate overdose risk (Dasgupta et al, 2015). Risk of overdose is increased among patients engaged in using opioids, alcohol, and illicit substances (Calcaterra et al, 2013; Cochran et al, 2016). Additionally, given that hydrocodone and oxycodone were the two most common opioids among those who engage in unhealthy alcohol use, increased risk of liver damage is of real concern considering these are commonly prescribed as combination products with acetaminophen.…”
Section: 1 Discussionmentioning
confidence: 99%
“…In 2010, 18.5% (n=81,365) of emergency department visits related to opioid pain medications also involved patient consumption of alcohol (Jones et al, 2014). Unhealthy alcohol use is a risk factor for opioid overdose (CDC, 2016; Cochran et al, 2016): overdose deaths rates are 0.63 per 100,000 lives for those who used both opioid medications and alcohol (Calcaterra et al, 2013). …”
Section: 1 Introductionmentioning
confidence: 99%